Learning disabilities practice concerns and students with LD - Bakken, Jeffrey P.; Obiakor, Festus E.; Rotatori, Anthony F. (Bingley, U.K. : Emerald, 2013)
This volume addresses the most current perspectives and issues related to learning disabilities and is written by leaders in the field of learning disabilities. The layout of the book and ordering of chapters will allow readers to follow learning disabilities in a very logical and thoughtful process from legal issues, identification, and assessment, to effective practices and response to intervention finally ending with practical issues of inclusion, working with families, and teacher preparation. Chapters can be read in order or independently which will allow readers considerable versatility. Chapters in the book include: Inclusion and Students with Learning Disabilities; Reading Instruction and Students with Learning Disabilities; Written Instruction and Students with Learning Disabilities; Mathematics Instruction and Students with Learning Disabilities; Social Skills Training and Students with Learning Disabilities; Response to Intervention Techniques and Students with Learning Disabilities; Transition and Students with Learning Disabilities; Technology and Students with Learning Disabilities; Families and Students with Learning Disabilities; Teacher Preparation and Students with Learning Disabilities.
Inclusion and learning disabilities : will the past be prologue? / Margo A. Mastropieri ... [et al.] -- Reading instruction and students with learning disabilities / Lisa V. McCulley, Sarah Katz, Sharon Vaughn -- Best practices and current trends in written instruction for students with learning disabilities / Linda H. Mason -- Common core state standards for mathematical practice : implications from a comprehensive review of the literature for teaching secondary students with LD / Paula Maccini, Jason A. Miller, Allyson P. Toronto -- Social skills training and students with learning disabilities / Mark P. Mostert -- Response to intervention techniques and students with learning disabilities / Temple S. Lovelace, Lenwood Gibson, JoVonne Tabb -- Transition from school to adult life for students with learning disabilities / Nicole M. Uphold -- Assistive technology for students with learning disabilities / Carrie Anna Courtad, Emily C. Bouck -- Families and students with learning disabilities / Christopher D. Yawn ... [et al.] -- Teacher preparation for student diversity and disabilities : changing roles in response to intervention models / Wendy Cavendish, Anabel Espinosa.
Print version record
Keywords: Education -- Special Education -- Learning Disabilities; Education -- Special Education -- General; Teaching of specific groups & persons with special educational needs; Teaching of students with emotional & behavioural difficulties; Learning disabilities